The Effectiveness of Deep Learning Training on Teachers' Memorization of Interactive Teaching Modules at MAN IC West Halmahera - Adiyana Adam; Ramli Yusuf; Muhlis Malaka; Minggusta Juliadarma; Mawardi Djamaluddin; Kamarun M. Sebe (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study aims to determine the effectiveness of deep learning training on teachers' abilities in developing interactive teaching modules at MAN Insan Cendekia West Halmahera. This study used a quantitative approach with a quasi-experimental design, with all teachers who participated in the training (n = 25) as samples. Data were collected through pre-tests and post-tests to measure teachers' abilities, a perception questionnaire to determine teachers' assessment of the training, and observations of the practice in creating interactive teaching modules. The results showed that the average teacher pre-test score of 56.2 increased to 80.6 in the post-test, with an average increase of 24.4 points or 43.4%, which was statistically significant (p < 0.05). Teachers also stated that the training was useful, relevant, and easy to implement in the learning process. Practical observations showed that teachers were able to create interactive teaching modules with media integration, adaptive quizzes, and animations that facilitate student understanding. These findings indicate that deep learning training is effective in improving teachers' skills and confidence in developing technology-based teaching modules. This research has important implications for teacher capacity development and learning innovation in schools.